‘We owe the world good theology’: On Reformed faith and public theology - Botha, JG (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
In this article certain perspectives found in the numerous publications by Dirkie Smit are related to three emphases in the legacy of German pastor and theologian, Dietrich Bonhoeffer. In thought as well as in praxis, Bonhoeffer 1) emphasised the importance of being there for and with others and 2) responded to the challenges of the immediate, complex context – the world – in which he was called to live and witness. 3) Finally Bonhoeffer, as a dedicated student of theology, emphasised the need for good theology in order to make a well-informed and well-grounded response to public discourse and life.